Anatomical study of common maidenhair fern ( Adiantum capillus-veneris L.) Pteridaceae, in Iraq - M. Ismail, Abbas; Al-Majmaie, Shaymaa (Al-Nahrain Journal of Science, 2023)
The family Pteridaceae in Iraq comprises 6 species belongs 5 genera. These species occur in a diverse range of environments including humid temperate forests, the falls of the waterfalls and shrub lands. The fern species was collected from different locations in environment and geographical habitats during different seasons from two districts in Iraqi Kurdistan. The anatomical structure of the aerial parts were studied. Fronds petiole and rachis (midribe) exhibit Y- shaped vascular system, pinnae were di chotomus venation, and the spores were pyramidal shape. The anatomical characterization of A. capillus-veneris were described with detail for the first time in Iraq.